Guidelines for Developing Internal Supervision in Basic Educational School in Nong Bua Daeng District, Chaiyaphum Province under Chaiyaphum Primary Educational Service Area 1 - Amphawa, Parinya; Duangchatom, Kritkanok (Interdisciplinary Academic and Research Journal, 2023)
Teaching and learning management after a period of time must be monitored to verify that Is the performance consistent with the objectives and goals of education management or not? This activity of monitoring and monitoring educational performance is called educational supervision. It is an activity that is coupled with educational administration. It is very important and necessary in the work process to achieve good efficiency and effectiveness. The purposes of this research were to 1) study the current and desirable conditions in the internal supervision of basic educational school, and 2) study the guidelines for developing the internal supervision of basic educational school. The research was divided into 2 stages as follows; the first stage studied the current and desirable conditions in the internal supervision of basic educational school. The sample was 422 teachers, and a questionnaire was utilized as a research tool having an Index Of item objective congruence (IOC) of 0.60 -1.00 and reliability index of 0.82. The second stage considered guidelines for developing the internal supervision of basic educational school. An interview form as a research tool was used for interviewing 9 experts, and data were analyzed from content analysis. As a result, this research revealed that (1) the current state of internal supervision in basic education school was at a high level overall and each side. The desirable condition in internal supervision of basic educational school was at the highest level overall and each side. (2) Guidelines for developing internal supervision of basic educational school was the development in internal supervision program of basic education school in Nong Bua Daeng District Chaiyaphum Province under Chaiyaphum Primary Educational Service Area 1 consisting of 1) principle, 2) objective, 3) content, 4) method of development and 5) measurement and evaluation. There were 5 modules, including Module 1 direct assistance to teachers, Module is professional development, Module 3 teamwork development, Module 4 curriculum development and Module 5 classroom action research. The five experts’ program evaluation result revealed that the overall evaluation results were appropriate at the highest level, and possibility was the highest level.